STUDENT’S CONTRIBUTION IN THE DIGITAL ERA TO PRESERVE CULTURE AROUND THE EAST JAVA REGION - Regina Cherryl Nathaniasuci; Muhammad Ikmal Razaq; Sherly Elysa Adijaya (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Nowadays, social media is very popular among people, especially young people. Through social media, all forms of interaction and communication can be created, through discussion and dissemination of information. This can be used as an opportunity to maintain and preserve regional culture, one of which is in the East Java area. Through various platforms, youth, especially students, can contribute to recognizing, maintaining, and preserving the culture in their area. Our research uses two methods, namely quantitative methods by distributing questionnaires through Google Forms to respondents, namely new students from Airlangga University Surabaya in all study programs with a limitation of 30 respondents from the Sidoarjo, Mojokerto, and Surabaya areas randomly. This study also uses a qualitative method through interviews with a young dancer from Sidoarjo who has had a lot of experience with his team in bringing dance performances from East Java. From here we can find out how much students are interested in preserving culture in East Java. It is hoped that through this activity we can also encourage and help people around us to start loving and getting to know the culture in East Java so that it remains sustainable by looking at the dominant interests of the respondents and with our creativity.